JIHAD PENISTA AGAMA JIHAD NKRI; Analisa Teori Hegemoni Antonio Gramsci terhadap Fenomena Dakwah Radikal di Media Online - Fatmawati Fatmawati; Kalsum Minangsih; Siti Mahmudah Noorhayati (Islam Futura, 2018)
This article will explore new trends of Islamic radicalism dakwah trough Jihad against penista agama (Ahok) as part of jihad NKRI. Trend of radical dakwah in online viral media is interesting researched, regardless of the importance of the election, or Khilafah and NKRI bersyariah on the other side. The purpose of this research is to know the trend of radical dakwah in online viral media by calling jihad against penista agama as part of jihad NKRI and how the implication of this dakwah. Questions from this study will be studied using the theory of domination of interests (hegemony), given the war of position of the radicals is to seize the hegemony of society through viral online media. In the conclusion, the use of the term Jihad against penista agama, as well as political branding that radical groups maintain the integrity of the NKRI is a hegemonic form to defeat the moderate, tolerant, and plural cultural power of Muslims. Those with the intellectual actors behind them, realizing that in order to gain legitimacy the religious power must collaborate with the MUI (fatwa institution), then play social media to invite all to participate and counter discourse. After that, share with interested politicians to advocate on the idea he was proposing. Finally, they use symbolic slogans of Islam to bring Muslims to the struggle that they do.